The psychology of evaluation: Addressing the pressures teachers face - Brown, Gavin Thomas Lumsden (Revista Contemporânea de Educação, 2023)
Evaluation processes are used to formatively inform improved instruction and summatively to determine the worth or value of teaching, schools, and students. These uses create pressures for teachers because they have conflicting goals around improvement vs. accountability. This perspective paper overviews the author’s understanding of evaluation, the challenges accountability presents to the conceptions teachers have about assessment and identifies a major obstacle to the impact of evaluation in the low information level of most so-called educational tests. A solution to the dilemma is recommended in the example of the Assessment Tools for Teaching and Learning software deployed in New Zealand schools.